OPTIMIZING CHILDREN"™S FUNDAMENTAL MOTOR SKILLS THROUGH TRADITIONAL GAMES IN THE CONTEXT PHYSICAL EDUCATION - Yulianto, Ari Gana; Faridah, Ai; Permana, Dian; Hamzah, Arief Adhitia; Santika, Bela (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study was motivated by the low level of fundamental movement skills in many students, which impacts their subsequent motor development. This experimental study, using a one-group pretestposttest design, aimed to improve the fundamental movement skills of first-grade elementary students (N=30; 16 males, 14 females; average age 6 years) through the implementation of traditional games in physical education classes. Data was collected using the Test of Gross Motor Development-Second Edition (TGMD-2) and analyzed quantitatively. The results showed a significant improvement in the fundamental movement skills of the students after the intervention with traditional games. This research contributes by demonstrating the effectiveness of traditional games as a fun and effective learning medium for enhancing fundamental movement skills in elementary students, providing practical implications for the development of more innovative and culturally-based physical education curricula. However, this study has limitations in terms of its relatively small sample size and its focus on first-grade students. Future research could expand the sample size, involve higher grade levels, and explore a wider variety of traditional games to optimize the improvement of fundamental movement skills.